Human Ratings of Writing Quality Capture Features of Syntactic Variety and Transformation in Chinese EFL Learners’ Argumentative Writing - Xue, Jin; Zheng, Liyan; Tang, Xiaoyi; Li, Banban; Geva, Esther (Frontiers in Psychology, 2021)
Traditionally, writing quality is measured by human ratings, either holistically or analytically. The present study aimed to investigate the locus of human ratings by analyzing the linguistic features that are predictive of writing quality. One hundred and forty-four argumentative writing samples from Chinese learners of English as a foreign language (EFL) were evaluated by human ratings and quantitative measurement of writing quality indexed by Coh-metrix. Holistic and analytic human ratings had significant correlations with quantitative measures related to syntactic variety and transformation. Moreover, linear and logistic regressions revealed that syntactic simplicity, words before main verb, syntactic structure similarity in all sentences and across paragraphs, incidence of passive voice and temporal connectives were five valid indices that can consistently differentiate writing quality indexed by human ratings. The present findings have significant pedagogical implications for human ratings on writing quality in the foreign language learning context.